Tony solves the linear equation 3(x - 3) + 2x + 9 = 2x + 2(x - 1) using the step shown below.

Step 1: 3x - 3+ 2x + 9 = 2x + 2x - 1
Step 2: 5x + 6 = 4x - 1

Step 3: 5x - 4x = -1 -6

Step 4: x=-7

What did he do wrong?

A) He incorrectly combined like terms.

B) He incorrectly applied the multiplication and division properties of equality.

C) He distributed incorrectly.

D) He incorrectly applied the addition and subtraction properties of equality.​

Answer :

me am saying he is correct

Answer:

He incorrectly combined liked terms

Step-by-step explanation: in step 3 5x and -4x should be on opposite sides.